2011
DOI: 10.1302/0301-620x.93b8.27132
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement and hemiarthroplasty in mobile, independent patients with a displaced intracapsular fracture of the femoral neck

Abstract: We reviewed the seven- to ten-year results of our previously reported prospective randomised controlled trial comparing total hip replacement and hemiarthroplasty for the treatment of displaced intracapsular fracture of the femoral neck. Of our original study group of 81 patients, 47 were still alive. After a mean follow up of nine years (7 to 10) overall mortality was 32.5% and 51.2% after total hip replacement and hemiarthroplasty, respectively (p = 0.09). At 100 months postoperatively a significantly greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
165
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(172 citation statements)
references
References 22 publications
6
165
1
Order By: Relevance
“…The mid-to long-term results of THA compared with hemiarthroplasty rarely were reported. Avery et al [1] reviewed the 7-to 10-year results of THA compared with hemiarthroplasty for fracture of the femoral neck and reported lower mortality and a trend toward superior function in patients with THA. Future studies comparing THA with hemiarthroplasty at long-term followup are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-to long-term results of THA compared with hemiarthroplasty rarely were reported. Avery et al [1] reviewed the 7-to 10-year results of THA compared with hemiarthroplasty for fracture of the femoral neck and reported lower mortality and a trend toward superior function in patients with THA. Future studies comparing THA with hemiarthroplasty at long-term followup are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published RSA data on 18 patients from Australia displayed a significant reduction of acetabular erosion in the bipolar group compared to the unipolar group at 24-months follow-up [18]. Furthermore, after a mean followup of nine years, Avery et al reported a rate of acetabular erosion of 100 % in the unipolar HA group, though only 13 of the original 41 patients were available for follow-up [23]. Of their 13 patients three (23 %) had enough symptoms due to acetabular erosion to justify revision surgery.…”
Section: Health-related Quality Of Life and Hip Functionmentioning
confidence: 99%
“…In general, symptomatic acetabular erosion following hemiarthroplasty occurs late and is not common. 13,18 Younger patients have been found to be at a higher risk for requiring revision surgery for acetabular erosion or loosening of the hemiarthroplasty than patients aged 75 years or older. 19 There may be an underestimation of the number of older patients with symptomatic hemiarthroplasties as many will not be suitable for revision owing to frailty and a lack of fitness for anaesthesia or further surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]13 Although patients may fit the criteria for THR as outlined by NICE, the selection of the right patients for THR remains difficult in clinical practice. For them to be strictly adhered to, guidelines should confer high efficacy but no attributable risk and they should help with difficult decisions, making the process easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation